Black and White, or Grey All Over? Lessons for Characters in and Viewers of a Hit TV Show about Work-related Identity, Ethics and Pedagogy - Kaela Jubas (Adult Education Research Conference, 2010)
This paper uses the television show Grey’s Anatomy to exemplify how popular culture functions as a source of informal adult learning related to work. Identity, ethics and pedagogy are explored as central themes of the show’s messages to audience members.